A TiO2 composite with graphitic carbon nitride as a photocatalyst for biodiesel production from waste cooking oil. Issue 59 (23rd November 2021) - Khan, Mahrukh; Farah, Humera; Iqbal, Naseem; Noor, Tayyaba; Amjad, M. Zain Bin; Ejaz Bukhari, Syeda Sidrah
Abstract : Catalyst TiO2 /g-C3 N4 composites was synthesized and tested for transesterification reaction of WCO at 60 °C (oil to methanol ratio 1 : 9) for 1 h. TiO2 / 20% g-C3 N4 with 2% catalyst concentration has the highest yield of biodiesel production (89.5%). Abstract : Semiconductor-based photocatalysts have attracted a lot of interest due to their environmental friendliness and high stability. Waste cooking oil can be converted to biodiesel by the process of transesterification. A TiO2 /g-C3 N4 combination was prepared by using a wet impregnation process. The photocatalyst was analyzed by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray spectroscopy (EDX), Thermogravimetric analysis (TGA), and Ultraviolet-visible spectroscopy (UV-vis). For effective transesterification, WCO was collected and acid-esterified to reduce the FFA concentration (below 3%). For the transesterification reaction, esterified WCO was used and the reactions were carried out under solar irradiation at 60 °C with an oil to methanol ratio of 1 : 9 and stirred for 1 hour, using different TiO2 /g-C3 N4 catalysts (10, 20 & 30%) with different catalyst concentrations of 1%, 2% and 3%. The results showed that TiO2 /20% g-C3 N4 with 2% catalyst concentration gives the highest yield of biodiesel production (89.5%) as compared to other catalyst concentrations used. In addition to (FTIR), additional fuel characteristics such as density, viscosity, flashpoint, acid value, and pH were tested to determine the quality of the generated biodiesel and were found to comply with fuel standards. With high stability and good catalytic activity, the synthesized composite TiO2 /g-C3 N4 is a viable option for producing biodiesel from WCO.